Headache in long COVID as disabling condition: A clinical approach - Rodrigues, Arthur Nascimento; Dias, Apio Ricardo Nazareth; Paranhos, Alna Carolina Mendes; Silva, Camilla Costa; Bastos, Thalita da Rocha; Brito, Bárbara Barros de; da Silva, Nívia Monteiro; de Sousa, Emanuel de Jesus Soares; Quaresma, Juarez Antônio Simões; Falcão, Luiz Fábio Magno (Frontiers in Neurology, 2023)
Background and purpose Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can exacerbate previous headache disorders or change the type of pain experienced from headaches. This study aimed to investigate the clinical features of Long COVID headaches. Method This was a cross-sectional, descriptive, and analytical observational study that included 102 patients (with previous headache, n = 50; without previous headache, n = 52) with long COVID and headache complaints. The Migraine Disability Assessment Test and Visual Analog Pain Scale were used to collect participants' headache data according to a standardized protocol. Results The patients in this study who reported experiencing headaches before COVID-19 had longer headache duration in the long COVID phase than that in the pre-long COVID phase (p = 0.031), exhibited partial improvement in headache symptoms with analgesics (p = 0.045), and had a duration of long COVID of <1 year (p = 0.030). Patients with moderate or severe disability and those classified as having severe headaches in the long COVID phase were highly likely to develop chronic headaches. Hospital admission [odds ratio (OR) = 3.0082; 95% confidence interval (95% CI): 1.10–8.26], back pain (OR = 4.0017; 95% CI: 1.13–14.17), insomnia (OR = 3.1339; 95% CI: 1.39–7.06), and paraesthesia (OR = 2.7600; 95% CI: 1.20–6.33) were associated with headache in these patients. Conclusion Headache is a disabling condition in patients with long COVID-19, exacerbating the conditions of those with headaches prior to contracting COVID-19.